Synthesis and Structural Characterization of Hydroxyapatite/TiO2 Nanocomposite Coatings for Potential Biomedical Applications - Kalaivani1, A.; Satheeshkumar2, P.; Senguttuvan2, G.; Sivakumar2, V.; Surendra Dilip3, C. (Asian Journal of Chemistry, 2013)
Hydroxyapatite ceramics have been recognized as substitute materials for bone and teeth in orthopeadic and dentistry fields due to their chemical and biological similarity to human hard tissue. Sol-gel technique has been developed and employed to prepare various materials because of easy control of homogeneity of the final product and low temperature synthesis. Hydroxyapatite/titania nanocomposites of different ratios are successfully synthesized by a simple sol-gel dip coating method. The coatings were done under controlled dipping and heat treatment processes. Further to heat treatment of the prepared nanocomposites, phase pure hydroxyapatite and TiO2 were found to be well developed and confirmed from the XRD studies. The SEM analysis of hydroxyapatite/TiO2 nanocomposite coatings shows the variation in morphology as a consequence different TiO2 concentration. EDAX analysis confirmed the presence of Ca, P, Ti and O. The FTIR studies established the presence of functional groups.